Historiografi Hisab Rukyah - Tasnim Rahman Fitra; Rahmadi (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2023)
The development of Hisab-Rukyah is not widely disclosed academically because Falak Science does not currently have its place in society. The development of Hisab Rukyah, of course, must be re-expressed to show that this science has had a special place in the midst of Islamic history. The development of reckoning rukyah at the time of the Prophet Muhammad was still at the level of worship and was still simple. At the time of the Companions, the development of reckoning rukyah was also not much different, but during the Caliph `Umar Ibn Khattab the Islamic calendar system was successfully formulated. During the tabi`in period, the development of reckoning and rukyah reached the peak of its progress during the reign of the Abbasids, especially the caliphate of al-Ma'mun. This is marked by the emergence of important figures and their works which later influenced the development of reckoning rukyah after that even to this day. In the Middle Ages, reckoning rukyah had experienced a setback due to the chaos of the Islamic world at that time, works in the field of astronomy were destroyed in an attack by the Mongols, but after that reckoning rukyah was able to rise again until modern times we are experiencing now.